ECB monetary policy surprises: identification through cojumps in interest rates - Lars Winkelmann; Markus Bibinger; Tobias Linzert (European Central Bank (ECB), 2014)
This paper proposes a new econometric approach to disentangle two distinct response patterns of the yield curve to monetary policy announcements. Based on cojumps in intraday tick-data of a short and long term interest rate, we develop a day-wise test that detects the occurrence of a significant policy surprise and identifies the market perceived source of the surprise. The new test is applied to 133 policy announcements of the European Central Bank (ECB) in the period from 2001-2012. Our main findings indicate a good predictability of ECB policy decisions and remarkably stable perceptions about the ECB's policy preferences.
Keywords: E58; C14; C58; 330; central bank communication; non-synchronous and noisy high frequency tick-data; spectral cojump estimator; Yield curve